China's Rising IQ (Innovation Quotient) and Growth : Firm-level Evidence - He, Hui (IMF Working Papers; Working Paper, 2016)
This paper examines whether the rapid growing firm patenting activity in China is associated with real economic outcome by building a unique dataset uniting detailed firm balance sheet information with firm patent data for the period of 1998-2007. We find strong evidence that within-firm increases in patent stock are associated with increases in firm size, exports, and more interestingly, total factor productivity and new product revenue share. Event studies using first-time patentees as the treatment group and non-patenting firms selected based on Propensity-Score Matching method as the control group also demonstrate similar effects following initial patent application. We also find that although state-owned enterprises (SOEs) on average have lower level of productivity and are less innovative compared to their non-state-owned peers, increases in patent stock tend to be associated with higher productivity growth among SOEs, especially for patents with lower innovative content. The latter could reflect the preferential government policies enjoyed by SOEs.